2020
DOI: 10.1063/1.5128132
|View full text |Cite
|
Sign up to set email alerts
|

CNOT gate operation on a photogenerated molecular electron spin-qubit pair

Abstract: Implementation of the two-qubit controlled-NOT (CNOT) gate is necessary to develop a complete set of universal gates for quantum computing. Here, we demonstrate that a photogenerated radical (spin qubit) pair within a covalent donor-chromophore-acceptor molecule can be used to successfully execute a CNOT gate with high fidelity. The donor is tetrathiafulvalene (TTF), the chromophore is 8-aminonaphthalene-1,8-dicarboximide (ANI), and the acceptor is pyromellitimide (PI). Selective photoexcitation of ANI with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 57 publications
0
72
0
1
Order By: Relevance
“…Figure S13). Some slights tructural broadening is observed in the wings of the spectrumd ue to 13 Cs atellite-transitions. [31] Compared to the spectrum of the trityl radical, the triplet state spectrumo fZ nTPP is very broad.…”
Section: à6mentioning
confidence: 95%
See 2 more Smart Citations
“…Figure S13). Some slights tructural broadening is observed in the wings of the spectrumd ue to 13 Cs atellite-transitions. [31] Compared to the spectrum of the trityl radical, the triplet state spectrumo fZ nTPP is very broad.…”
Section: à6mentioning
confidence: 95%
“…[3,[8][9][10] In the area of molecular spintronics, photogenerated organic multi-spins ystems have proven invaluable for exploring the fundamental requirements for spin-information transfer and storageo namolecular level. [11][12][13][14] By photoexcitation, well-defined initial spin states with strongs pin polarisation can be generated, which may then be characterisedb ya dvanced magnetic resonance techniques with regard to their magnetic properties and spin-spin interactions. Through systematic variationso ft he molecular design and ac areful study of the resultingm agnetic properties, it will ultimately be possible to establishd esign protocols for new magnetic materials exhibiting the desired properties for an efficient transfer and storage of spin information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47] Tuning spin-orbit coupling in molecular systems and their subsequent trESR signatures, as demonstrated here, is not only of paramount importance to blue OLED development but may also find resonance more broadly in the development of organic materials for light-controlled quantum information and spintronics. [78][79][80][81][82]…”
Section: Ct D and Ementioning
confidence: 99%
“…Photoexcitation has been used to generate S > 1/2 systems for a long history, with many examples showing quantum entanglement or long coherence times 19,[33][34][35][36] . Recent researches have demonstrated that a photogenerated radical pair can be utilized to perform quantum teleportation in a donor-acceptor stable radical system 37 .…”
Section: Introductionmentioning
confidence: 99%